W trosce o Matkę Ziemię. Zarys biblijnego tła encykliki „Laudato si’” - Wajda, Anna Maria (Verbum Vitae, 2017)
The following article presents an outline and examination of the biblical background of the encyclical "Laudato si’". These biblical-ecological issues are considered especially in Chapter II of the encyclical, which is entitled "The Gospel of Creation". According to Pope Francis, the passages in Genesis relating to human dominion over the created world cannot be understood as justification for the unbridled exploitation of nature. In fact, the encyclical does not attempt to offer an exhaustive presentation of the biblical theology of creation, but, significantly, this church document emphasizes the importance of human agency in a world created by God. Man is supposed to be a good manager and host, the gardener of the Earth, who oversees its welfare in order to preserve nature and the planet for future generations.